2018
DOI: 10.1155/2018/6125901
|View full text |Cite
|
Sign up to set email alerts
|

Motor Improvement of Skilled Forelimb Use Induced by Treatment with Growth Hormone and Rehabilitation Is Dependent on the Onset of the Treatment after Cortical Ablation

Abstract: We previously demonstrated that the administration of GH immediately after severe motor cortex injury, in rats, followed by rehabilitation, improved the functionality of the affected limb and reexpressed nestin in the contralateral motor cortex. Here, we analyze whether these GH effects depend on a time window after the injury and on the reexpression of nestin and actin. Injured animals were treated with GH (0.15 mg/kg/day) or vehicle, at days 7, 14, and 35 after cortical ablation. Rehabilitation was applied a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
33
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 15 publications
(36 citation statements)
references
References 71 publications
3
33
0
Order By: Relevance
“…There were clear implications of GH in the opioid system function in which it was able to decrease levels of the delta-opioid receptor in layers I–IV of the cerebral cortex [ 87 ]. In brain trauma, GH has demonstrated neurotrophic actions in the cognitive, sensorial, and motor functions [ 57 , 58 , 88 , 89 ]. In an experimental model for brain contusion recovery, GH improved cognitive function and increased the brain-derived neurotrophic factor (BDNF) and TrkB in the prefrontal area [ 73 ].…”
Section: Expression and Neurotrophic Effects Of Growth Hormone (Ghmentioning
confidence: 99%
“…There were clear implications of GH in the opioid system function in which it was able to decrease levels of the delta-opioid receptor in layers I–IV of the cerebral cortex [ 87 ]. In brain trauma, GH has demonstrated neurotrophic actions in the cognitive, sensorial, and motor functions [ 57 , 58 , 88 , 89 ]. In an experimental model for brain contusion recovery, GH improved cognitive function and increased the brain-derived neurotrophic factor (BDNF) and TrkB in the prefrontal area [ 73 ].…”
Section: Expression and Neurotrophic Effects Of Growth Hormone (Ghmentioning
confidence: 99%
“…During the post-acute period these hormones also improve the lost cognitive functions; specific neurostimulation, including EINA, is of great help for enhancing the neuroregenerative effects of GH and facilitating the creation of new neuronal circuits that would replace the lost ones after the SAH, perhaps because facilitating brain plasticity, as we recently demonstrated in rats treated with GH after a severe frontal motor cortex ablation [36,64].…”
Section: Resultsmentioning
confidence: 90%
“…Furthermore, there is now building evidence demonstrating that GH treatment in addition to standard rehabilitation can significantly contribute to the motor recovery of an acquired brain injury [9][10][11][12][13][14][15][16][17][18][19][20][21][22][23][24]37,46,47]. For instance, Heredia et al [18,37] observed that administration of GH subcutaneously together with rehabilitation significantly improved motor function in rats as measured by the paw-reaching-for-food task. Therefore, we were motivated to extend the existing preclinical literature to consider GH treatment for its ability to ameliorate motor impairments after stroke [14].…”
Section: Discussionmentioning
confidence: 99%
“…The therapeutic potential of GH on brain repair after brain injury or stroke has been considered in both human [9][10][11][12][13][14][15][16][17][18] and preclinical [19][20][21][22][23][24] studies. GH, a peptide hormone released from the anterior pituitary gland, plays an important role in brain growth, development and function [11].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation